Sex differences in ambulatory blood pressure among patients referred for 24-hour monitoring - Hasan Atmaca; Doğaç Çağlar Gürbüz; Mustafa Kemal Erol; Ertan Yetkin (Medicine, 2026)
Few studies have addressed the differences between hypertensive women and men regarding the diagnosis and control of blood pressure (BP). Accordingly, we aimed to assess the possible discrepancies in BP values between women and men who underwent 24-hour ambulatory blood pressure monitoring. The study population comprised all patients who underwent 24-hour ambulatory blood pressure monitoring, which was retrospectively screened and recorded. Demographic and clinical characteristics of 1204 patients were included in the analysis. Sex-specific analyses of all patients, including those with and without a former diagnosis of hypertension (HT), were performed. Two-thirds of the patients were women. In the general population, both systolic and diastolic BP levels in women were significantly lower than those in men. BP in women was also significantly lower than that in men, both in patients with and without a former diagnosis of HT. Our study demonstrated that women exhibited significantly lower systolic and diastolic BP values than men in this referral cohort, irrespective of a prior diagnosis of HT. While the exact mechanisms remain to be elucidated, this difference highlights the necessity for further research into sex-specific hemodynamic profiles. Consequently, further research is necessary to establish diagnostic thresholds and BP targets to achieve effective and targeted management of BP abnormalities in women.